OAUNI photometry of ASASSN-16hw - Pereyra, Antonio (2016)
We report optical photometry of Type Ia SN ASASSN-16hw (=SN 2016ekt, ATel #9278, ATel #9289, ATel #9300) on 2016-08-06 (UT) gathered with the OAUNI 51cm telescope (Pereyra et al. 2015;arXiv:1512.03104) at Huancayo Observatory, Peru. CCD imaging measurements using V and R broadband filters were acquired with seeing ~1.9" and airmass = 1.5. A total integration time of 42x20s=840s in each filter yielded: Date (UT) filter mag 2016-08-06.119 R 14.656 +/- 0.003 2016-08-06.120 V 14.497 +/- 0.004 Field stars were used for the zero point calibration. Following PESSTO and Du Pont classifications (ATel #9289, ATel #9300), our measurements are very close to maximum. The OAUNI project is supported by UNI, TWAS, IGP and Cienciactiva (Convenio 102-2015 Fondecyt).